Շփումը՝ որպես անձի բազային պահանջմունք - Արտյոմ Ղևոնդյան (ՀՀ ԳԱԱ հրատ.)
В статье рассматривается категория общения как базовая (основная) потребность человека. Дается определение общения, выделяются его виды, функции и типы. Идея формирования общения приводится виде небольшого исторического экскурса. Большое внимание уделено мнению ведущих мировых экспертов. Рассматриваются и анализируется выдвинутые ими спорные идеи. This article is about communication as a basic (main) need of a person. The definition for communication is formulated, its types, functions and classes are differentiated. Reference is made to the origin of the concept of communication in a form of a small historical excursus as well as a great attention is drawn to the opinions of the world’s leading experts. Contradicting ideas put forward by them are considered and analyzed.
Keywords: Philosophy